Comparison of the anatomical structure of two populations of the relict species Populus pruinosa Schrenk (Salicaceae Mirb.) growing in the Aktobe region - Turalin, B.A.; Atayeva, G.A.; Moldekova, I.Zh.; Syrymbetov, S.T.; Abdukarimov, A.; Abidkulova К.Т.; Kurbatova, N.V.; Saksebay, A.K. (Fundamental and Experimental Biology, 2023)
The article presents the results of a study of the anatomy of the vegetative organs (shoots, buds, leaf blades, and petioles) of Populus pruinosa Schrenk. The studied species are part of the vulnerable, tertiary relict species has status 2 (U) in the floristic complex of the Aktobe region The research material was collected in two populations of Populus pruinosa Schrenk: the first population grows in the Irgiz region, 10 km southeast of the village. Tauip, 143 m a.s.l., N 48.11267°, Е 62.11620° the second population is in the Irgiz region, 35 km (Zhylandy area) in the southern part of the village. Nura 167 m a.s.l., N 48,74523°, Е 62,51491° the species grows on sands and pebbles, solonchaks singly or in groves along rivers, which have undergone anatomical and morphological studies at the microscopic and macroscopic levels.The choice of the topic was made in accordance with the endemicity, significance, and relevance of biodiversity conservation issues. Nat-ural populations are of particular importance for research because they reflect many aspects of interest to science, such as the life cycle, anatomical structure, and life expectancy. The obtained information about the features of the anatomical structure of the vegetative organs of Populus pruinosa Schrenk will be used in the future for the diagnosis of this species when studying its phytochemical composition.